2013
DOI: 10.1021/ml400269v
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Reactivity Descriptors to Assess the Aromatic Stacking within the Tyrosine Gate of FimH

Abstract: Antagonists of the FimH adhesin, a protein almost universally present at the extremity of type-1 fimbriae expressed by Escherichia coli, have been abundantly in the spotlight as alternative treatments of urinary tract infections. The antagonists function as bacterial antiadhesives through highly specific α-d-mannose binding in a charged and polar pocket at the tip of the FimH lectin domain and by the stacking of alkyl or aromatic moieties substituted on the mannose with two tyrosine residues (Tyr48 and Tyr137)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 12 publications
1
44
0
Order By: Relevance
“…Ligand entry into the sugar pocket is framed by the ‘tyrosine gate’ residues, which also line the hydrophobic groove [80]. Key π-stacking and van der Waals interactions occur within this flexible gate region, and it has been demonstrated that the binding affinity of a mannoside can be largely affected by the ability of the aglycone to orient properly within the tyrosine gate [81]. The flexibility of the gate is due to the dynamic ability of Tyr48 to rotate between three positions: an open-gate configuration, where the residue is positioned toward Asp47; a closed-gate configuration, where Tyr48 is aligned towards the Thr51; or spatially somewhere between the two positions, in a half-open-gate configuration (Fig.…”
Section: Structural Biology Of Type 1 Pili Fimh and Its Lectin D-mentioning
confidence: 99%
“…Ligand entry into the sugar pocket is framed by the ‘tyrosine gate’ residues, which also line the hydrophobic groove [80]. Key π-stacking and van der Waals interactions occur within this flexible gate region, and it has been demonstrated that the binding affinity of a mannoside can be largely affected by the ability of the aglycone to orient properly within the tyrosine gate [81]. The flexibility of the gate is due to the dynamic ability of Tyr48 to rotate between three positions: an open-gate configuration, where the residue is positioned toward Asp47; a closed-gate configuration, where Tyr48 is aligned towards the Thr51; or spatially somewhere between the two positions, in a half-open-gate configuration (Fig.…”
Section: Structural Biology Of Type 1 Pili Fimh and Its Lectin D-mentioning
confidence: 99%
“…[11a, 15d] As an experimental verification, n-butyl a-d-mannoside (9) [11a] and severalm onoaryl antagonists [27] have been co-crystallized with FimH-CRD in both the open and the closed forms. Wellens et al proposed that the open conformation represents the minimum-energy conformer of FimH and that the closed conformation is only stabilized by favorable interactions with hydrophobic aglycones.…”
Section: X-ray Crystal Structures Of Fimhwith Antagonistsmentioning
confidence: 99%
“…Unfortunately,i nm any FimH-mannoside co-crystal structures the binding pocket residues or the ligand are involved in crystal lattice contacts potentially affecting the binding pocket geometry. [26][27] Therefore, more experiments are needed to study the structure and dynamics of FimH-antagonist complex formation in solution.…”
Section: X-ray Crystal Structures Of Fimhwith Antagonistsmentioning
confidence: 99%
“…These approaches are classified as global reactivity descriptors (GRD). They became wide-spread in recent times because electronic structure calculations are easier to perform due to the increase in computational power [25,26]. The above mentioned GRD arise naturally from conceptual density functional theory (DFT), as they can be described in terms of the electron density as follows The concept of chemical hardness (η) was developed from the formulation of Parr and Pearson [32].…”
Section: Introductionmentioning
confidence: 99%